Ireland's helping hand to Europe : combatting hunger from Normandy to Tirana, 1945-1950 - De Wiel, Jérôme aan, 1966- (Central European University Press, 2021)
"Post-war Marshall Plan aid to Europe and indeed Ireland is well documented, but practically nothing is known about simultaneous Irish aid to Europe. This book provides a full record of the aid - mainly food but also clothes, blankets, medicines, etc. - that Ireland donated to continental Europe, including France, the Netherlands, Hungary, the Balkans, Italy, and zones of occupied Germany. Starting with Ireland's neutral wartime record, often wrongly presented as pro-German when Ireland in fact unofficially favoured the western Allies, Jerome aan de Wiel explains why Éamon de Valera's government sent humanitarian aid to the devastated continent. His book analyses the logistics of collection and distribution of supplies sent abroad as far as the Greek islands. Despite some alleged Cold-War hijacking of Irish relief - and this humanitarianism was not above the politics of that East-West confrontation - it became mostly a story of hope, generosity and European Christian solidarity. Rich archival records from Ireland and the European beneficiary countries, as well as contemporary local and national newspapers across Europe, allow the author to measure and describe not only the official but also the popular response to Irish relief schemes. This work is illustrated with contemporary photographs and some key graphs and tables that show the extent of the aid programme"--